Outcompeting Thermodynamics: Ion-Pairing and Coulombic Interactions to Trigger Perfluoroacetate Intra-Ionic Photooxidation for Perfluoroalkylation Reactions - Li, Pengju; Bourgois, Céline; Glaser, Felix; De Kreijger, Simon; Cadranel, Alejandro; Troian-Gautier, Ludovic; Hu, Ke (Journal of the American Chemical Society, 2025)
Trifluoromethylation is a key transformation in drug and agrochemical synthesis, yet current reagents often suffer from high cost, low atom economy, and low scalability. Trifluoroacetate derivatives represent ideal reagents as they are highly abundant and cheap, but their very positive one electron oxidation potential (∼2.3 V vs NHE) often hampers their widespread use in photoredox catalysis. Indeed, at these potentials, selectively oxidizing trifluoroacetate over reaction solvent or partner substrates becomes challenging. Herein, we present a novel approach that circumvents these limitations through the use of a pentacationic Ir(III) photosensitizer that forms a strong 1:1 ion-pair with trifluoroacetate in acetonitrile (Keq = 6 × 104 M-1). This ion-pair formation enables rapid and efficient photooxidation of trifluoroacetate in ∼90 ps without significant solvent or partner substrate oxidation, as indicated by femtosecond and nanosecond UV-visible transient absorption spectroscopy. The CF3• radicals so generated are shown to trifluoromethylate a range of partner substrates, including aromatic compounds, heterocycles, natural products and pharmaceutically relevant products, in moderate yields (20-60%). Control experiments reveal that ion-pairing is crucial for the successful generation of CF3• as photosensitizers that oxidize trifluoroacetate without forming ion pairs were ineffective for trifluoromethylation. This probably originates from the more thermodynamically accessible substrate oxidation outcompeting diffusional trifluoroacetate oxidation. The reaction was further exemplified to allow functionalization with a variety of perfluoroalkyl groups of different chain lengths. The approach reported herein could also be used for the removal and/or use of perfluoroalkyl substances (PFAS), often called “forever chemicals”, that have recently raised environmental and health concern.
CRIS-Team Scopus Importer:2025-04-11